Wage System for Workers in The Confectionery Company - Wiryawan, I Wayan Gde; Apriliani, Kadek (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2024)
A decent living is a standard requirement for an employee or single worker to live physically well within a month. To fulfill this, the government has established regulations so that the wages earned by workers can meet their basic living needs. This study discusses the wage system in Indonesia, as well as the Wage System for Workers at PT Wedanata Industri Nusantara in Badung, Bali. The methodology used is an empirical juridical research methodology, approaching facts occurring in the field related to the legal issues examined. The aim of this research is to understand the implementation of wage regulations in conversion companies. It can be concluded that Indonesia has regulations governing wages and wage systems.